PENGARUH PEMBERIAN ASI EKSKLUSIF DAN PENGETAHUAN IBU TENTANG PEMBERIAN MAKANAN TAMBAHAN PADA BAYI SEBELUM USIA ENAM BULAN TERHADAP STATUS BALITA DI DESA NOELBAKI KABUPATEN KUPANG - Kadek Dwi Ariesthi (Universitas Citra Bangsa, 2020)
Breastfeeding is one component of reproduction which consists of menstruation, conception, pregnancy, childbirth, breastfeeding, and weaning. If this component goes well, the breastfeeding process is also successful. This study aims to determine the effect of exclusive breastfeeding and maternal knowledge about supplementary feeding to infants before the age of six months on toddler status. This type of research is a descriptive study with the type of cross sectional approach. The research was conducted from September to October 2019 in Noelbaki Village, Kupang Regency, which consisted of 114 mothers as respondents. Data was collected by conducting interviews directly at the home of each respondent. Data analysis was carried out bivariately to determine the direction of the relationship between the independent variable and the dependent variable. Based on the results of the study, it was found that the mother's knowledge about breastfeeding before the baby was 6 months had a significant relationship with the nutritional status of toddlers with exclusive breastfeeding while exclusive breastfeeding was not related to nutritional status